Priority based flow control protocol for internet of things built on light fidelity - Vatsala, Belathuru Ramanna; Chitradurga, Vidyaraj (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Excessive usage of Internet by most of the applications that use internet of things (IoT) has resulted in need for high bandwidth network. Light fidelity (LiFi) is one such network having bandwidth in terms of GigaHertz, but LiFi has a limited propagation range hence it can be deployed only in the local area. When IoT nodes are connected using LiFi network in the local area they start pushing large data to the cloud there by arising need for flow control. Some of the IoT applications such as patient monitoring systems and nuclear systems, generate critical data. The protocol for flow control in this case should be based on priority of data since critical data with high priority have to be transmitted first. We develop a flow control protocol named priority based flow control protocol (PFCP) by providing priority to flows that carry critical data especially in IoT system that use LiFi network. We evaluate performance of different transmission control protocol (TCP) variants and modify TCP variant that yields maximum goodput according to the priority based protocol developed and demonstrate that flows that carry critical data are given priority compared to non-prioritized flows